Local peacebuilding and national peace : interaction between grassroots and elite processes - Mitchell, C. R. (Christopher Roger), 1934-; Hancock, Landon E., 1964- (London ; New York : Continuum, 2012)
"Local Peacebuilding and National Peace is a collection of essays that examines the effects of local peacebuilding efforts on national peace initiatives. The book looks at violent and protracted struggles in which local people have sought to make their own peace with local combatants in a variety of ways, and how such initiatives have affected and have been affected by national level strategies. Chapters on theories of local and national peacemaking are combined with chapters on recent efforts to carry out such processes in warn torn societies such as Africa, Asia, and South America, with essays contributed by experts who were actually actively involved in the peacemaking process. With its unique focus on the interaction of peacemaking at local and national levels, the book will fill a gap in the literature. It will be of interest to students and researchers in such fields as peace studies, conflict resolution, international relations, postwar recovery and development." -- Publisher's website.
Introduction : linking national-level peacemaking with grassroots peacebuilding / Christopher Mitchell -- A ZoPs approach to conflict prevention / Wallace Warfield and Yves-Reně Jennings -- Against the stream : Colombian zones of peace under democratic security / Christopher Mitchell and Catalina Rojas -- Colombia : from grassroots to elites : how some local peacebuilding initiatives became national in spite of themselves / Mery Rodriguez -- South Africa's infrastructure for peace / Andries Odendaal -- Belfast's interfaces, zones of conflict or zones of peace / Landon E. Hancock -- Zones of peace in the South Caucasus : polyphonic approaches to state-building / Irakli Zurab Kakabadze -- Between local and national peace : complementarity or conflict? / Landon E. Hancock and Christopher Mitchell.
Includes bibliographical references and index.
Keywords: Peace-building.; Peace; International relations; International relations; Peace; Peace-building.; PEACEBUILDING; CONFLICT MANAGEMENT; INTERNAL SECURITY; COMMUNITY DEVELOPMENT; POLITICAL ASPECTS; CASE STUDIES